KANDUNGAN GULA ES KRIM YANG DISUKAI MAHASISWA DEPOK - Ibnu Malkan Bakhrul Ilmi; Firlia Ayu Arini; Avliya Quratul Marjan; Salsabila Firdausiyah Nur Habieb (PERSATUAN AHLI GIZI INDONESIA, 2023)
The prevalence of obesity in Indonesia is always increasing every year. Depok City occupies the second position with the highest prevalence of obesity in West Java. One of the causes of obesity is the habit of consuming foods containing added sugar such as ice cream. This is supported by the opening of many ice cream shops. This study aims to look at the description of ice cream consumption habits in college students, the amount of sugar content in ice cream and the relationship between ice cream consumption habits and nutritional status. The method used is descriptive observational to see the habit of consuming ice cream. Habits include frequency, preference, and type of ice cream. The questionnaire was distributed online via social media. Laboratory tests were carried out to see the content of macronutrients and sugar content (glucose, sucrose and fructose). The data analysis used was crosstabulation and chi-square test. The number of students involved was 938 students from 34 universities in Depok City. The nutritional status of Depok students was mostly normal (65.6%). Most Depok college students often eat ice cream with a frequency of 1-2 times a week. There are 83 types of ice cream variants that are often consumed by Depok students. The content of ice cream consumed was in the range of protein 2.6 - 3.7 gr, fat 4.4-7.06 gr, carbohydrates 24.3-76.1 gr, total sugar 13.2-30.0, and total calories of 154.1-383.1 kcal. There is no relationship between ice cream consumption habits and the nutritional status of Depok students (p=0.679). Ice cream contributes to fulfilling 7-20 percent of RDI and half of the daily sugar recommendation, so it is necessary to limit the consumption of ice cream. ABSTRAK Prevalensi obesitas di Indonesia selalu mengalami peningkatan setiap tahunnya. Kota Depok menempati posisi kedua prevalensi obesitas tertinggi di Jawa Barat. Salah satu penyebab kejadian obesitas adalah kebiasaan mengonsumsi makanan mengandung gula tambahan seperti es krim. Hal ini didukung dengan banyak dibuka toko es krim. Penelitian ini bertujuan untuk melihat gambaran kebiasaan konsumsi es krim pada mahasiswa, jumlah kandungan gula pada es krim serta hubungan kebiasaan konsumsi es krim dengan status gizi. Metode yang digunakan adalah observasional deskriptif untuk melihat kebiasaan konsumsi es krim. Kebiasaan meliputi frekuensi, preferensi, dan jenis es krim. Kuesioner disebarkan secara online melalui media sosial. Uji laboratorium dilakukan melihat kandungan zat gizi makro dan kandungan gula yaitu glukosa, sukrosa dan fruktosa. Analisis data yang digunakan yaitu crosstabulation dan uji chi-square. Jumlah mahasiswa yang terlibat sebanyak 938 mahasiswa yang berasal dari 34 universitas di Kota Depok. Status gizi mahasiswa Depok sebagian besar normal (65,6%). Sebagian besar mahasiswa Depok sering mengonsumsi es krim dengan frekuensi 1-2 kali seminggu. Jenis varian es krim yang sering dikonsumsi mahasiswa Depok sebanyak 83 jenis. Kandungan es krim yang dikonsumsi berada pada rentang protein 2,6 – 3,7 gr, lemak 4,4 – 7,06 gr, karbohidrat 24,3 – 76,1 gr, gula total 13,2-30,0 serta total kalori sebesar 154,1-383,1 kkal. Tidak terdapat hubungan antara kebiasaan konsumsi es krim dengan status gizi mahasiswa Depok (p=0,679). Es krim berkontribusi memenuhi 7-20 persen kebutuhan gizi serta setengah rekomendasi gula harian, sehingga perlunya dibatasi konsumi es krim. Kata kunci: es krim, gula, kalori, mahasiswa